Hydroxychloroquine Reverses Platelet Activation Induced by Human IgG Antiphospholipid Antibodies - Espinola, Ricardo G.; Pierangeli, Silvia S.; Ghara, Azzudin E.; Harris, E. Nigel (Thrombosis and Haemostasis, 2002)
Prothrombotic properties of antiphospholipid (aPL) antibodies may be explained in part by their ability to enhance the activation of platelets pre-treated with low doses of ADP or thrombin. The antimalarial drug hydroxychloroquine (HQ) has been used successfully in prevention of postoperative thrombosis and in treatment of patients with SLE or APS. In one study, administration of HQ reversed the thrombogenic properties of aPL in mice. However, the mechanism of action of HQ in preventing thrombosis is not clearly understood. In order to explore this further, the effects of HQ on activation of platelets by aPL in the presence of a thrombin agonist was studied. The changes in the expression of GPIIb/IIIa (CD41a) and GPIIIa (CD61) on platelet membrane by flow cytometry were used as indicators of platelet activation. Citrated whole blood from a healthy donor was treated at room temperature with suboptimal doses of a thrombin agonist receptor peptide (TRAP) and affinity-purified aPL antibodies, in the presence and in the absence of hydroxychloroquine (1 mM). TRAP increased the expression of GPIIb/IIIa and GPIIIa on platelet surface. The treatment of the platelets with the six aPL antibodies in the presence of 12 nMol/ml TRAP further increased the expression of GPIIb/IIIa by 42.3 ± 12.3% and the expression of GPIIIa was further incremented by 46.8 ± 13.5%. The effects of aPL and TRAP on expression of platelet surface markers of activation was completely abrogated by HQ in a dose-dependent fashion and was effective at concentrations of HQ as low as 25 µg/ml (0.0125 mM). This suggests at least one possible mechanism by which HQ may prevent thrombosis. This may have important implications in treatment of thrombosis in APS patients.
Keywords: Antiphospholipid antibodies; platelet activation; hydroxychloroquine; thrombosis; GPIIb/IIIa